Impacts of future changes in climate variability on Europe’s renewable electricity systems - L van der Most; K van der Wiel; R M J Benders; P W Gerbens-Leenes; R Bintanja (Environmental Research: Climate)
The shift toward renewable energy as part of Europe’s climate-neutral strategy increases the energy system’s reliance on weather conditions. This study explores the impacts of changes in climate variability and extremes on Europe’s renewable electricity systems, affecting reliability. It uses a large ensemble approach integrating 1600 years of climate data under present-day (PD) and +2 °C warming scenarios into a modeling framework for wind, solar, and hydropower production alongside electricity demand. The study assesses changes in mean states, variability, and extremes, identifying rare, high-impact events, e.g., energy droughts and multi-year low electricity production. The results reveal notable regional and seasonal variations in energy system dynamics under future warming scenarios. In the Nordic region, increased winter runoff leads to higher hydropower availability, reducing residual loads and shortening energy drought durations. In contrast, Iberia faces growing challenges with extended summer cooling demands, exacerbated by reduced wind and hydropower availability. Importantly, the analysis shows that changes in extremes differ significantly from mean trends, with deviations up to −20% (overestimation) or +4% (underestimation) in the most severe scenarios. Decadal variability analysis underscores the critical influence of natural climate modes like the Atlantic Multidecadal Variability (AMV) and the North Atlantic Oscillation on energy production and demand. In the PD ensemble, the AMV shows strong correlations with energy variables (0.93 for mean demand anomalies and >0.73 for wind power). However, the +2 °C warming scenario reduces the statistical significance of these correlations. This study highlights the importance of explicitly analyzing extremes, as mean trends alone may misrepresent (changes in) system risks. By explicitly accounting for both natural variability and climate change, it provides insights into extreme compound events, giving a foundation for robust, adaptive strategies to ensure energy system reliability in a changing climate.